PENGARUH LITERASI KEUANGAN SYARIAH TERHADAP MINAT MAHASISWA MENGGUNAKAN PRODUK PAYLATER NON SYARIAH - Angel Chandra Septin; Zainal Abdul Haris; Retno Widiastuti (Politeknik Negeri Malang, 2023)
The study aims to determine the effect of Islamic financial literacy level on interest in using non-sharia PayLater products. The type research is quantitative research. The data collection technique used questionnaire distributed online to students of the State Polytechnic of Malang accounting department class of 2018-2021. The sampling technique used nonprobability sampling, as many as 95 people. The data analysis of this study was Simple Linear Regression Analysis by using SPSS version 26 software. The results of this study showed that the level of Islamic financial literacy had no effect on students' interest in using non-sharia PayLater products with a t count of -242 (<1.989) and a significance value of 0.809 (>0.05). The value of the coefficient of determination (R2) is 0.001, which means that the variable ability of islamic financial literacy levels in explaining students' interest in using non-sharia PayLater products is 0.1%.